Very low energy diets prior to bariatric surgery may reduce postoperative morbidity: a systematic review and meta-analysis of randomized controlled trials - McKechnie, Tyler; Lee, Yung; Dionne, Joanna; Doumouras, Aristithes; Parpia, Sameer; Bhandari, Mohit; Eskicioglu, Cagla (Frontiers in Nutrition, 2023)
Purpose: To optimize patients prior to bariatric surgery, very low energy diets (VLEDs) are often employed for 2-4 weeks preoperatively. They are known to result in preoperative weight loss, decrease liver volume, and decrease surgeon perceived operative difficulty. Their impact on postoperative morbidity has been less extensively studied. We performed a focused systematic review and meta-analysis with the aim of comparing preoperative VLEDs prior to bariatric surgery to controls in terms of overall postoperative morbidity Methods: MEDLINE, Embase, and CENTRAL were searched from database inception to February 2023. Articles were eligible for inclusion if they were randomized controlled trials (RCTs) comparing adult patients (i.e., over the age of 18) receiving either a VLED with liquid formulation or a non-VLED control prior to elective bariatric surgery in terms of postoperative morbidity. Outcomes included overall 30-day postoperative morbidity and preoperative weight loss. An inverse variance meta-analysis was performed with GRADE assessment of the quality of evidence. Results: After reviewing 2,525 citations, four RCTs with 294 patients receiving preoperative VLEDs with liquid formulation and 294 patients receiving a non-VLED control met inclusion. Patients receiving VLED experienced significantly more preoperative weight loss than patients receiving control (Mean Difference (MD) 3.38 kg, 95% Confidence Interval (CI) 1.06-5.70, p=0.004, I2=95%). According to low certainty evidence, there was a non-significant reduction in 30-day postoperative morbidity in patients receiving VLED prior to bariatric surgery (Risk Ratio (RR) 0.67, 95%CI 0.39-1.17, p=0.16, I2=0%). Conclusion: The impact of preoperative VLEDs on postoperative outcomes following bariatric surgery remains unclear. It is possible that VLEDs may contribute to decreased postoperative morbidity, but further larger prospective trials are required to investigate the signal identified in this study.